Prevalence and factors associated with illicit drug and high-risk alcohol use among adolescents living in urban slums of Kampala, Uganda - Hellen Kalungi; Onesmus Kamacooko; Jane Frances Lunkuse; Joy Namutebi; Rose Naluwooza; Matt A. Price; Eugene Ruzagira; Yunia Mayanja (BMC, 2024)
Abstract Background Illicit drug and high-risk alcohol use among adolescents leads to poor health outcomes. We enrolled adolescents from urban slums in Kampala, Uganda, to assess baseline prevalence and factors associated with illicit drug and high-risk alcohol consumption. Methods We conducted a cross-sectional study using data collected in a cohort that enrolled 14-19-year-old male and female participants from 25 March 2019 to 30 March 2020. Data was collected on social demographics, sexual behavior, and reproductive health using interviewer-administered questionnaires. The main outcomes were illicit drug use and high-risk alcohol use. Data on alcohol use was collected using the Alcohol Use Disorder Identification Test (AUDIT); results were dichotomized. Factors associated with each outcome were analyzed using multivariable logistic regression. Results We enrolled 490 participants (60.6% female) with a median age of 18 (IQR 17-18) years, 84.9% had less than secondary education, 48.4% had their sexual debut before 15 years, 47.1% reported paid sex in the past 3 months and 22.8% had a sexually transmitted infection (chlamydia, gonorrhea, and active syphilis) baseline characteristics associated with illicit drug use in the past 3 months were male gender (aOR 12.45; 95% CI 7.21-21.50) being married (aOR 2.26; 95%CI 1.03-4.94) 10 or more paying sexual partners (aOR 2.45; 95%CI 1.05-5.69) and high-risk alcohol use (aOR 3.94; 95%CI 2.10-7.40), baseline characteristics associated with high-risk alcohol use were male gender (aOR 0.29; 95% CI 0.13-0.63) emotional violence from sexual partners (aOR 2.35; 95%CI 1.32-418) illicit drug users com (aOR 3.94; 95% CI 2.10-7.40). Conclusion Illicit drug and high-risk alcohol use are prevalent among male adolescents and adolescents involved in high-risk sexual behavior living in the urban slums of Kampala.